Analisis Inovasi dan Teknologi dalam Layanan Rawat Jalan Rumah Sakit Mata pada Masa Pandemi COVID-19 - Andreasih, Chika; Dhamanti, Inge (LPPM Hang Tuah Pekanbaru, 2024)
ABSTRACT The pandemic has had an impact on efforts to provide services at eye hospitals. The implications are related to services with the role of outpatient service preparedness and technological innovation. Objective: By Knowing the various management of outpatient services in eye hospitals during the COVID-19 pandemic, it is hoped that it can help increase patient safety rates and reduce the occurrence of errors in handling COVID-19. Method: The method used in the research is a literature review. Article searches use keywords, namely